The protective effect of hesperetin in osteoarthritis: an in vitro and in vivo study. Issue 3 (11th March 2020) - Lin, Zeng; Fu, Changchang; Yan, Zijian; Wu, Yifan; Zhan, Jingdi; Lou, Zhiling; Liao, Xin; Pan, Jun
Abstract : Osteoarthritis (OA), a progressive joint disorder, is principally characterized by the degeneration and destruction of articular cartilage. Abstract : Osteoarthritis (OA), a progressive joint disorder, is principally characterized by the degeneration and destruction of articular cartilage. Previous research studies demonstrated that inflammation and ECM degradation play a major role in OA development. Hesperetin, the aglycone of neohesperidin found in the peel of Citrus aurantium L. (Rutaceae), demonstrated in several studies potential anti-inflammatory activity in a variety of diseases. However, the mechanisms by which hesperetin plays a protective role in osteoarthritis (OA) are not completely understood. In this study, we found the anti-inflammatory effects of hesperetin in the progression of OA in both in vitro and in vivo experiments. In vitro, IL-1β-induced expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nitric oxide (NO), tumor necrosis factor alpha (TNF-α), prostaglandin E2 (PGE2), and interleukin-6 (IL-6) were inhibited by hesperetin. Moreover, hesperetin down-regulated the IL-1β-stimulated matrix metalloproteinase-13 (MMP-13) and thrombospondin motifs 5 (ADAMTS-5) while up-regulating collagen type II and aggrecan. Mechanistically, we revealed that hesperetin suppressed nuclear factor kappa B (NF-κB) signaling by activating the nuclear factor (erythroid-derived 2)-like 2 (Nrf2) in IL-1β-induced chondrocytes. Hesperetin-induced repression of OA development is shown using a DMM model. Taken together, our findings suggest that hesperetin may be a novel potential therapeutic agent for repressing the development of OA.